Internetökonomie der Medienbranche - Hagenhoff, Svenja (Universitätsverlag Göttingen, 2006)
Products and services of the media industry can be digitized completely and distributed in electronic form. This fact makes the media industry more tangent to all innovations in information and communications technology than any other industries. The German Federal Ministry of Education and Research (BMBF) funds the Göttingen research project Mediaconomy, where changes in the media industry, which have been caused by internet technology, are being looked at from the point of view of different disciplines: library science, informatics, law, sociology and commercial information technology. In nine particular projects with focus on the mobile internet on the one hand and communications in sciences on the other hand explanatory models for phenomena of the internet economy are being developed.